Spindle and Round Cell Sarcoma With EWSR1-PATZ1 Gene Fusion: A Sarcoma With Polyphenotypic Differentiation. (February 2019) - Chougule, Abhijit; Taylor, Martin S.; Nardi, Valentina; Chebib, Ivan; Cote, Gregory M.; Choy, Edwin; Nielsen, G. Petur; Deshpande, Vikram
Abstract : The evolving classification of round cell sarcomas is driven by molecular alterations. EWSR1-PATZ1 fusion positive spindle and round cell sarcoma is one such new tumor entity. Herein, we report 2 EWSR1-PATZ1 fusion positive spindle and round cell sarcomas with overlapping histologic features and polyphenotypic differentiation. The intra-abdominal tumors affected female patients, 31-and 53-year old. Both tumors showed sheets and nests of round to spindle cells, fine chromatin, tiny conspicuous nucleoli, moderate cytoplasm, and thick bands of intratumoral fibrosis. On immunohistochemistry, both tumors showed positivity for CD99, desmin, myogenin, MyoD1, S100, Sox10, CD34, and GFAP and were negative for keratin. Fluorescence in situ hybridization revealed rearrangement at EWSR1 locus. Next-generation sequencing–based RNA fusion assay revealed EWSR1-PATZ1 fusion in both cases. EWSR1-PATZ1 fusion positive spindle and round cell sarcomas show abundant intratumoral fibrosis and polyphenotypic differentiation, thus mimicking a range of tumors including desmoplastic small round cell tumor. The precise classification of this spindle and round cell sarcoma and its relationship to the Ewing sarcoma family of tumors remains to be determined. Abstract : Supplemental Digital Content is available in the text.